Respuesta :

We can plug those values into the equation, and if the answer is incorrect, we'll know if either one is extraneous.

√11 - 2(-7) = √(-7)^2 + 4(-7) + 4

√25 = √25

5 = 5

The first solution, -7, makes the equation true, and so it is not extraneous.

√11 - 2(1) = √(1)^2 + 4(1) + 4

√9 = √9

3 = 3

The second solution, 1, makes the equation true, and so it is also not extraneous.

The correct option is D, neither solution is extraneous.


Answer:

D.) Neither solution is extraneous.

Step-by-step explanation: